The Effect of Digital Transformation, Business Innovation Models, and Creativity on MSME Performance with Competitive Advantage as Intervening Variable - Adisaksana, Helmy (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The purpose of this study was to determine the effect of digital transformation, business innovation model, and creativity on MSME performance with a competitive advantage as an intervening variable. The research method used is quantitative research. The population was all MSMEs in the city of Malang. The sample is determined by the convenience sampling technique. In this study, researchers involved as many as 100 MSMEs in the city of Malang. Based on the research conducted, it was found that there was no influence between the digital transformation variables on performance. There is a significant positive effect between digital transformation variables on competitive advantage. There is a significant positive effect between the competitive advantage variables on performance. There is a significant positive effect between the variables of creativity on performance. There is a significant positive effect between the variables of creativity on competitive advantage. There is a significant positive effect between the variables of the business innovation model on performance. There is no effect between the variables of creativity on competitive advantage. There is a significant positive effect between the variables of digital transformational effect on performance mediated by competitive advantage. There is no influence between the variables of the effect of the business innovation model on performance mediated by competitive advantage. There is a significant positive effect between the variables. The influence of creativity on performance is mediated by competitive advantage.